Capital requirements and bank behavior in the UK: Are there lessons for international capital standards? - Francis, William B.; Osborne, Matthew (Journal of Banking & Finance, 2012)
The financial crisis prompted widespread interest in developing a better understanding of how capital regulation drives bank behavior. This paper uses a unique, comprehensive database of regulatory capital requirements on all UK banks to examine their effects on capital, lending and balance sheet management behavior. We find that capital requirements that include firm-specific, time-varying add-ons set by supervisors affect banks’ desired capital ratios and that resulting adjustments to capital and lending depend on the gap between actual and target ratios. We use these results to measure the effects of a capital regime that includes features similar to those embedded in the UK framework. Our results suggest that countercyclical capital requirements may be less effective in slowing credit activity when banks can readily satisfy them with lower-quality (lower-costing) capital elements versus higher-quality common equity. Given the size of the UK banking sector and the global nature of many of the largest institutions in the UK banking sector, the results have implications for the ongoing debate surrounding the design and calibration of international capital standards.